Evaluating soil fertility of various agricultural lands using soil evaluation factor (sef) at tropical uplands in Sarawak - Soo Ying, Ho; Mohd Effendi, Wasli; Mugunthan, Perumal (2016)
Rapid population expansion throughout decades has put tremendous pressure on the agricultural land resources across the globe including Malaysia. With increasing cases of land degradation, the awareness in conserving the soil resources slowly gained attention from policymakers and public society. Soil quality indicators were developed by scientists to quantify large-scale evaluation systems including integrated natural resource management framework and soil fertility capability (Sanchez et al. 2003). Soil Fertility Index (SFI) has been implemented by Moran et al. (2000) to determine the relationship between soil fertility and rate of secondary forest succession. Subsequently, Lu et al. (2002) improved the equation by introducing Soil Evaluation Factor (SEF) to evaluate the secondary forests succession at Brazil under different types of soils (Alfisols, Ultisols, and Oxisols). Few researchers have been adapted these indices to estimate the soil fertility and quality of secondary forests in Southeast Asia (Doi and Sakurai 2004; Arifin et al. 2008). Additionally, Panwar et al. (2011) further proposed these indices to determine the impact of different land uses including forest plantation, home garden, areca nut plantation and agricultural land on soil fertility of Entisols in India. However, the applicability of these indices in estimating the soil fertility under tropical upland soils has not been commonly practiced in Malaysia. Thus, this study aimed to determine the soil fertility at various agricultural land uses cultivated with rubber, oil palm and pepper using Soil Evaluation Factor (SEF) in comparison with the adjacent secondary forests at tropical uplands in Sarawak.